2008
DOI: 10.1678/rheology.36.167
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Viscoelastic Behavior of Aqueous Hybrid Threadlike Micellar Solutions

Abstract: Nonlinear viscoelastic behavior of aqueous hybrid threadlike micellar solutions consisting of cetyltrimethylammonium bromide (CTAB) and sodium poly(styrene-ran-sodium styrenesulfonate) (P(St/NaSS)) in water was investigated. Strain-hardening behavior well described with a three-(freely jointed)-chain model was observed when start-up shear flows at shear rates sufficiently higher than the reciprocal of the longest relaxation times were applied to the solutions. The size of segments, which is a reasonable measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…[21][22][23][24] We recently reported that some aqueous HTM systems also showed strain-hardening behavior. 25) However, strain-hardening behavior has been merely observed in the concentrated polymer systems, which only show shear-thinning behavior. According to Inoue et al, 23,24) the mechanism of strain-hardening behavior is attributed to the finite extensibility of the threadlike micelles forming fused temporal cross-linking between two threadlike micelles at entanglement points.…”
Section: Nonlinear Viscoelastic Behaviormentioning
confidence: 99%
“…[21][22][23][24] We recently reported that some aqueous HTM systems also showed strain-hardening behavior. 25) However, strain-hardening behavior has been merely observed in the concentrated polymer systems, which only show shear-thinning behavior. According to Inoue et al, 23,24) the mechanism of strain-hardening behavior is attributed to the finite extensibility of the threadlike micelles forming fused temporal cross-linking between two threadlike micelles at entanglement points.…”
Section: Nonlinear Viscoelastic Behaviormentioning
confidence: 99%